2014
DOI: 10.1042/cs20140087
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNAs in cancers of the female reproductive tract: insights from recent clinical and experimental discovery studies

Abstract: microRNAs (miRNAs) are small RNA molecules that represent the top of the pyramid of many tumorigenesis cascade pathways as they have the ability to affect multiple, intricate, and still undiscovered downstream targets. Understanding how miRNA molecules serve as master regulators in these important networks involved in cancer initiation and progression open up significant innovative areas for therapy and diagnosis that have been sadly lacking for deadly female reproductive tract cancers. This review will highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 335 publications
(186 reference statements)
1
16
0
Order By: Relevance
“…There are 14 studies that use only serous histotype samples (Supplemental Table 1) and 13 studies that mix histotypes in the same study (Supplemental Table 2). Since our two previous reviews (5, 25), the published studies for comprehensive microRNA profiling studies in EOC have expanded greatly in number and sophistication of experimental design. Clinical associations of specific microRNA molecules in EOC tissues are listed in Supplemental Table 3.…”
Section: Microrna Molecules As Clinical Biomarkers For Eocmentioning
confidence: 99%
See 1 more Smart Citation
“…There are 14 studies that use only serous histotype samples (Supplemental Table 1) and 13 studies that mix histotypes in the same study (Supplemental Table 2). Since our two previous reviews (5, 25), the published studies for comprehensive microRNA profiling studies in EOC have expanded greatly in number and sophistication of experimental design. Clinical associations of specific microRNA molecules in EOC tissues are listed in Supplemental Table 3.…”
Section: Microrna Molecules As Clinical Biomarkers For Eocmentioning
confidence: 99%
“…Improved screening approaches to detect early stage disease and novel histotype- or molecular-marker specific therapies for the treatment of late stage disease are urgently needed. This review highlights clinical associations of microRNA molecules and microRNA machinery, including DROSHA, DICER, and Argonaute proteins, in EOC identified since our last review (5). The clinical relevance of these potential new biomarkers as prognostic, diagnostic, and therapeutic molecules are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently endometrial oncogenesis was connected with alterations of microRNAs expression [2]. And a number of studies including our own research reported microRNAs as promising diagnostic and prognostic factors in EC [35].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the gene subset enriched for abnormal morphology had mRNA targets predominantly regulated by let-7, miR-125b, and miR-24. For example, miR-205, miR-24, and miR-21 are highly expressed in cervical cancers compared to normal controls [49]; and miR-205 is thought to play a role in cervical cancer or serve as a diagnostic marker in plasma [22, 50]. Downregulation of miR-203 and upregulation of let-7 and miR-21 are associated with early stage and invasive cervical carcinoma [51].…”
Section: Discussionmentioning
confidence: 99%
“…The same investigators have linked these changes to reduced fetal growth [21]. Moreover, a number of miRNAs have been identified as associated with ovarian and cervical cancers (as reviewed in [22]) demonstrating that these biomarkers are biologically active in the reproductive system. Previously, we have shown that metal exposure affects the expression of specific miRNAs in blood from occupationally exposed individuals [23] and that miRNAs in the cervix during pregnancy are associated with subsequent gestational age at delivery [24], but metal-altered miRNA expression has not yet been investigated with respect to tissues involved in parturition and labor.…”
Section: Introductionmentioning
confidence: 99%